PHILOSOPHICAL INTENTIONS IN THE HUMANITARIAN TRAINING OF OIL AND GAS ENERGY SPECIALISTS - Скальська, Д.; Ілюк, Т.Ю. (SWorldJournal, 2025)
The article reveals the features of humanitarian training of oil and gas specialists through the actualization of philosophical prerogatives in the educational process. Based on a comprehensive approach to the problem, the need to involve philosophical in